2021
DOI: 10.5219/1501
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characteristics of eggs of chickens of domestic and foreign selection in their diverse age

Abstract: At this juncture, more and more attention is drawn to the preservation of the gene pool of local breeds of poultry, which have a set of valuable features, including high-quality eggs. In this study, the quality parameters of eggs (egg weight, weight, and proportion of yolk, weight, and proportion of albumen, yolk-albumen ratio, energy value, lipid and fatty acid content in the yolk) of chickens of Ukrainian selection(such hybrids as Plymouth white, Poltava Clay, Birkivska Barvysta and their interbreed hybrids)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(6 reference statements)
0
1
0
2
Order By: Relevance
“…Є чимало досліджень учених з різних країн, які проведені за використання курей кросів, селекціонованих у компанії "Hy-Line International" Ren et al, 2020;Cabezas-Garcia et al, 2022). Порівняльні дослідження щодо якості яєць курей різних кросів та вітчизняних порід і ліній провели українські вчені (Nalyvayko et al, 2021). При цьому, слід зазначити, що виробництвом власної племінної продукції наразі в Україні займається тільки Державна дослідна станція птахівництва НААН, але вона може забезпечувати потреби лише невеликих фермерських і присадибних господарств (Катеринич, 2020).…”
Section: анотація в україні для виробництва курячих харчових яєць вик...unclassified
“…Є чимало досліджень учених з різних країн, які проведені за використання курей кросів, селекціонованих у компанії "Hy-Line International" Ren et al, 2020;Cabezas-Garcia et al, 2022). Порівняльні дослідження щодо якості яєць курей різних кросів та вітчизняних порід і ліній провели українські вчені (Nalyvayko et al, 2021). При цьому, слід зазначити, що виробництвом власної племінної продукції наразі в Україні займається тільки Державна дослідна станція птахівництва НААН, але вона може забезпечувати потреби лише невеликих фермерських і присадибних господарств (Катеринич, 2020).…”
Section: анотація в україні для виробництва курячих харчових яєць вик...unclassified
“…At the same time, other studies (Orobchenko et al, 2022) confirmed that while the bromine in chicken eggs does not exceed the WHOapproved dose for people, equaling 0.4 mg/kg of body weight (WHO, 2018), the intake of bromine with chicken eggs in 2020 has increased by 1.6-2.0 times, compared with 2016. Taking into account bromine's ability to accumulate (Du Toit & Casey, 2011, 2012Koreneva, 2020) and the popularity of poultry products (Nimalaratne & Wu, 2015;Nalyvayko et al, 2021), the objective of our study was determining the influence of high-bromine poultry products the level of thyroid hormones and clinicalbiochemical blood parameters of white rats.…”
Section: Introductionmentioning
confidence: 99%
“…Chicken eggs are one of the most useful products in the daily diet of a person, especially children. They contain all the necessary nutrients and biologically active substances easily absorbed by the human body [19], [20], [28]. In addition to protein, fats (fatty acids), enzymes, and vitamins, egg white and yolk also contain minerals (macroand micronutrients).…”
Section: Introductionmentioning
confidence: 99%